Comparative fascist studies : new perspectives - Iordachi, Constantin 1970- Hrsg (Rewriting histories, 2010)
"Owing to its mass appeal, revolutionary and violent nature, strong political impact, and multiple reverberations in contemporary politics, fascism was one of the most complex, and hotly debated movements of the twentieth century. Comparative Fascist Studies: New Perspectives brings together some of the leading experts in the field in order to provide an informative introduction to the most recent debates on fascist studies and the history of fascism across Europe. In his general, analytical introduction Constantin Iordachi focuses on transnational approaches to fascism, briefly reviewing the comparative method and its application to fascist studies. Concentrating on the interwar period, the book is divided into three parts, offering a synoptic overview of the latest developments in the field, exploring different definitions of fascism, and grounding these theoretical debates in their historical context. The three parts correspond to distinct methods and levels of comparison. They focus on: debates over ideal-type models of generic fascism used as instruments of comparison, and evaluation of historic case studies; cross-national and trans-national comparisons of historical examples of fascism, measured against each other or against theoretical models of generic fascism; and debates over totalitarianism and political religions and their relevance for studying fascist movements and regimes."--Publisher's description